(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2024)
The development of broiler chicken farming agribusiness is the whole activity from upstream, process, and downstream, which can increase the productivity of profit-oriented livestock businesses in order to realize the revitalization of agricultural development. The present study aimed to analyze the development of broiler chicken farming agribusiness. This study was carried out at Campus IV Unkhair, Bangko, West Halmahera Regency, taking into account that this location was the center for the development of Agro-Ecotourism Educational Park integrated with agriculture, animal husbandry, and fisheries. The type of this study was a survey research using qualitative methods, which were quantitatively expressed in reel numbers. The variables observed included the production facilities provider subsystem, production subsystem, marketing subsystem, and supporting institutions subsystem. Data were analyzed using the Analytical Hierarchy Process (AHP)with the aim of understanding the indicators for the development prospects of agribusiness integration of organic vegetables and broiler chicken farming by determining criteria and selecting alternative strategies based on similar characteristics in decision making. The results indicated that the priority scale was in the marketing subsystem criteria, meaning that marketing was an important part in developing broiler chicken agribusiness on farms, which connected production and consumption activities.